Profit Sharing System Business Ship Unit Fishing Divers on The Island of Barrang Lompo, Makassar City - Rasul, Abdul; Baso, Aris; Amiluddin, Amiluddin; Fakhriyyah, Sitti; Gosari, Benny Audy Jaya (PONGGAWA : Journal of Fisheries Socio-Economic, 2023)
This study aims to determine the income of the unit of sea cucumber dive fishing boats on Barrang Lompo Island, Makassar City to find out the profit sharing system for sea cucumber fishermen on Barrang Lompo Island, Makassar City. This research was carried out in Sangkarrang Subdistrict, Barrang Lompo Village, Makassar City in July 2021. The type of research used was descriptive qualitative and quantitative by using tools in the form of questionnaires with interview and observation techniques as the main data collection methods. Based on the results of research on the business of sea cucumber divers on Barrang Lompo Island, Sangkarrang District, it can be concluded that the average income of sea cucumber fishermen on Barrang Lompo Island per year is Rp. 406.361,422. The profit-sharing system contained in the sea cucumber dive fishing vessel unit is 25: 75, where the retainer or ship owner has a profit of Rp. 101,590,355/year and mustard or crew members have a profit of Rp. 22,507,998/year.